Late Pre-Emergent Control of Annual Bluegrass with Flazasulfuron & Indaziflam - J. Reeves; J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2016)
All applications of flazasulfuron or indaziflam resulted in acceptable control of Annual Bluegrass (Poa annua), only allowing<3% visual weed cover (VWC) in all treatments compared to the non-treated (26% VWC) up to 133 days after application (DAA).
Keywords: weed control; pre-emergent; annual bluegrass